Async executors in Rust : Tokio and Async-Std (Manning Publications Co., 2021)
Ever since the 2018 edition's introduction of the async syntax, there have been several executors to actually run that new type of Rust code. Tokio was leading the charge and is now the most popular framework to execute Futures in Rust - but it is not alone. How do contenders such as async-std compare? Is async-std better? In this session Claus Matzinger explores state-of-the-art Rust async frameworks to see which one you should use for your next project.